Mosquito Larvae Monitoring Program toward on Free Larvae Index and House Index in Kampung Bebas Jentik, Cilandak - Tobing, Tiffanny Ocktivianie (HIGEIA (Journal of Public Health Research and Development), 2023)
ABSTRACT The implementation of Mosquito Larvae Monitoring Program has been implemented in several areas in Cilandak district. The highest incidence rate in Pondok Labu and Gandaria Selatan sub-districts have ranked as the 1st and 9th. The objective of this study was measure the success rate of the mosquito larvae monitoring program based on the increase in the Free Larvae Index and House Index that were not in line with increased in the incidence rate of Dengue. This was cross sectional study with quantitative descriptive analysis and qualitative methods using univariate analysis to analyze Mosquito Larvae Monitoring Reports from January to August and in-depth interview with 8 Jumantik. The result showed that in Pondok Labu sub-district the FLI (Mean= 98.29; SD= 0.63) and HI (Mean= 1.68; SD= 0.61) and Gandaria Selatan sub-district the FLI (Mean= 97.90; SD= 0.68) and HI (Mean= 21.20; SD= 0.72). The success of the mosquito larva monitoring program doesn’t only focus on the results of the indicators, but also the reduction in morbidity and larvae in that area. ABSTRAK Kecamatan Cilandak merupakan daerah yang telah menerapkan pemantauan jentik nyamuk, namun di daerah ini masih diperhadapkan pada beban penyakit DBD, dengan angka kejadian tertinggi di Kelurahan Pondok Labu dan Gandaria Selatan yang menempati peringkat ke-1 dan ke-9. Tujuan dari penelitian ini adalah untuk mengukur tingkat keberhasilan program pemantauan jentik nyamuk berdasarkan peningkatan Free Larvae Index dan House Index yang tidak sejalan dengan peningkatan angka kejadian DBD. Penelitian ini merupakan penelitian cross sectional dengan analisis deskriptif kuantitatif dan metode kualitatif yang menggunakan analisis univariat untuk menganalisis Laporan Pemantauan Jentik dari Januari – Agustus 2022 dan wawancara mendalam dengan 8 Jumantik. Hasil penelitian menunjukkan bahwa di Kelurahan Pondok Labu FLI (Mean= 98,29; SD= 0,63) dan HI (Mean= 1,68; SD= 0,61) dan Kelurahan Gandaria Selatan FLI (Mean= 97,90; SD= 0,68) dan HI (Mean= 21.20; SD= 0.72). Keberhasilan program pemantauan jentik nyamuk tidak hanya terpaku pada hasil indikator, akan tetapi juga penurunan angka kesakitan dan jentik di wilayah tersebut.